Surgical approach of the dentigerous cyst - Saenz-Quiroz, Lizardo (2014)
This clinical case report presents the sequence of surgical treatment of a dentigerous cyst and intraoperative complication of displacement of the tooth within the cyst. The dentigerous cyst is the second most common odontogenic cyst. It is generally associated with the crown of an impacted normal tooth, usually with lower third molars and maxillary canines. One of the surgical treatment (enucleation) of the cysts is indicated in cases where complete removal of pathological tissue is required and even removal of the teeth involving odontogenic cysts; however, if treatment is not done they can become other dental pathologies involving adjacent pieces to injury. Clinical sequence of surgical approach is presented for extracting a tooth associated with a dentigerous cyst.